2006
DOI: 10.1159/000097893
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Attenuates Acute Hyperglycaemia-Induced Endothelial Cell Apoptosis, Leucocyte-Endothelial Cell Interactions and Cardiac Dysfunction

Abstract: Objectives: Hyperglycaemia is implicated in microvascular inflammatory injury and subsequent cardiac injury/dysfunction. Leucocyte adhesion to the endothelium, migration into tissue and toxic metabolite release are early critical steps. Taurine is a semi-essential amino acid that is endothelial protective and restrains excess leucocyte activity by the formation of less toxic inflammatory mediators. The aim was to establish if taurine reduces acute hyperglycaemia-induced endothelial cell apoptosis and leucocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 74 publications
2
22
0
1
Order By: Relevance
“…It has been shown that taurine attenuates acute hyperglycemia-induced apoptosis of endothelial cells [39]. The present study has also demonstrated that taurine reduced cellular apoptosis of multiple organs induced by II/R.…”
Section: Discussionsupporting
confidence: 79%
“…It has been shown that taurine attenuates acute hyperglycemia-induced apoptosis of endothelial cells [39]. The present study has also demonstrated that taurine reduced cellular apoptosis of multiple organs induced by II/R.…”
Section: Discussionsupporting
confidence: 79%
“…However, co-incubation of aortas with 5-10 mM taurine concentration-dependently prevented both the hyperglycemiainduced alterations in vascular smooth muscle contractility and endothelium-mediated vasorelaxation, the effects being more pronounced at higher concentrations. Although a protective effect of taurine against toxicity caused by hyperglycemia in endothelial cells has been reported (Wu et al, 1999;Casey et al, 2007), the present observation is the first of its kind regarding the effect of the nutrient on intact vascular preparation. Further demonstrating the significance of these data, hyperglycemiainduced hypertension in rats has been shown to be normalized with in vivo treatment with taurine, while blood pressure of control animals was not altered by the nutrient (Casey et al, 2007).…”
Section: Discussionmentioning
confidence: 54%
“…The expression of intracellular adhesion molecule-1 (ICAM-1), which mediates cell-cell adhesion, was decreased by taurine in Sprague-Dawley rats with impaired ROS scavenging capability. Taurine given intravenously at 200 mg/kg for 5 days before the induction of inflammation prevented a significant increase in the expression of ICAM-1 in the post-capillary venules (high endothelial cell region) (6). The production of tumor necrosis factor-α (TNF-α), an important pro-inflammatory cytokine, has been shown to be down-regulated through a multitude of mechanisms including substrate depletion and uncoupling of eNOS (24).…”
Section: Discussionmentioning
confidence: 99%